2013
DOI: 10.1128/jvi.01412-13
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Vesicular Stomatitis Virus in an Immunocompetent Model of MUC1-Positive or MUC1-Null Pancreatic Ductal Adenocarcinoma

Abstract: Vesicular stomatitis virus (VSV) is a promising oncolytic agent against various malignancies. Here, for the first time, we tested VSV in vitro and in vivo in a clinically relevant, immunocompetent mouse model of pancreatic ductal adenocarcinoma (PDA). Our system allows the study of virotherapy against PDA in the context of overexpression (80% of PDA patients) or no expression of human mucin 1 (MUC1), a major marker for poor prognosis in patients. In vitro, we tested three VSV recombinants, wildtype VSV, VSV-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 84 publications
(103 reference statements)
0
21
1
Order By: Relevance
“…Although the exact mechanism of oncoselectivity of such non-replicating VSV particles is unclear, the study showed that, compared to normal cells, the cancer cells were more sensitive to replication-deficient VSV-mediated cell death due to their defective type I IFN signalling [53]. In contrast to this study, one of our own studies showed that UV-killed VSV-DM51-GFP enhanced tumour growth in an immunocompetent mouse model of pancreatic ductal adenocarcinoma (PDAC) [54]. The mechanism is unclear and will be examined in our future studies.…”
Section: Attenuation Of Vsv Through Disruption Of Normal Gene Ordercontrasting
confidence: 74%
See 2 more Smart Citations
“…Although the exact mechanism of oncoselectivity of such non-replicating VSV particles is unclear, the study showed that, compared to normal cells, the cancer cells were more sensitive to replication-deficient VSV-mediated cell death due to their defective type I IFN signalling [53]. In contrast to this study, one of our own studies showed that UV-killed VSV-DM51-GFP enhanced tumour growth in an immunocompetent mouse model of pancreatic ductal adenocarcinoma (PDAC) [54]. The mechanism is unclear and will be examined in our future studies.…”
Section: Attenuation Of Vsv Through Disruption Of Normal Gene Ordercontrasting
confidence: 74%
“…Combining VSV with chemical agents Previously, combining VSV with the chemotherapeutic drug doxorubicin improved therapeutic effect [87]. Our own group combined VSV-DM51-GFP with the chemotherapeutic drug gemcitabine and observed improved antitumour efficacy in a mouse PDAC xenograft model [54]. It has been previously shown that combining VSV with obatoclax, a B-cell lymphoma 2 (Bcl-2) inhibitor, reversed resistance of cancer cells to VSV-mediated oncolysis [88].…”
Section: Increasing Direct Oncotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…and centrifuged at 4,000 × g for 10 min at 4°C to remove large cellular debris. Virus was purified by the method of Kalvodova et al with slight modifications described previously (Hastie et al, 2013; Kalvodova et al, 2009). Cell specific viral titers were obtained using plaque assay.…”
Section: Methodsmentioning
confidence: 99%
“…[73][74][75][76][77][78][79][80][81][82] Each has shown modest to promising success when combined with a VSV OV in cancer cells and/or murine tumor models. Some chemotherapeutics, such as Sunitinib and rapamycin, suppress the antiviral response, which sensitizes resistant tumors to OV therapy.…”
Section: Coupling Oncolytic Rhabdovirus Therapy With Additional Cancementioning
confidence: 99%